The effects of a four week primary and secondary speed training protocol on 40 yard sprint times in female college soccer players - Wagganer, J. D.; Williams, R. D.; Barnes, J. T. (Journal of Human Sport & Exercise, 2014)
Improvements in running speed have been attributed to both primary and secondary speed training techniques. Primary techniques involve attention to running mechanics and form, and secondary techniques involve resisted or assisted sprinting. The purpose of this study was to assess the effect of combining both primary and secondary speed training techniques on 40 yard sprint speed in young soccer players. PURPOSE: To compare the effects of pre- and post- four week speed training protocol on 40-yard sprint times in female collegiate soccer players. METHODS: Twelve (19.5+1.5y) normal weight (BMI: 22.7+3.4 kg·m-2) and body composition (BF: 27.75+3.8%) active white female collegiate soccer players participated in a four week training protocol which implemented primary and secondary speed training methods. A standard running mechanics program was implemented two times per week and was immediately followed by resisted or assisted sprinting. Sled towing was chosen for resisted sprinting, while elastic towing devices were chosen for assisted sprinting. Forty yard sprint times were assessed pre and post protocol. Statistical analysis was conducted using SPSS. RESULTS: A paired samples t-test showed the four week speed training protocol elicited statistically significant reductions in 40 yard sprint times (p<0.001). The average sprint time decreased by 0.248 seconds (pre=5.463+0.066 vs post=5.215+0.053). CONCLUSION: A four week speed training protocol of primary and secondary techniques may play a significant role in reducing 40 yard sprint times in college female soccer athletes. Values are presented as (mean+SEM)